2007
DOI: 10.1093/jxb/erm143
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-mediated remote control of reversible sieve tube occlusion in Vicia faba

Abstract: According to an established concept, injury of the phloem triggers local sieve plate occlusion including callose-mediated constriction and, possibly, protein plugging of the sieve pores. Sieve plate occlusion can also be achieved by distant stimuli, depends on the passage of electropotential waves (EPWs), and is reversible in intact plants. The time-course of the wound response was studied in sieve elements of main veins of intact Vicia faba plants using confocal and multiphoton microscopy. Only 15-45 s after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
185
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(189 citation statements)
references
References 54 publications
3
185
1
Order By: Relevance
“…In conclusion, forisome dispersion may have a lower Ca 2+ threshold than callose synthesis. 13 EPWs (as in Fig. 2) were recorded only at distance of 0.1-0.5 cm from the site of cutting; the electrical signal steeply decreased with the distance (Fig.…”
Section: Wounding Reactions and Passage Of Epws After Cutting The Maimentioning
confidence: 88%
See 4 more Smart Citations
“…In conclusion, forisome dispersion may have a lower Ca 2+ threshold than callose synthesis. 13 EPWs (as in Fig. 2) were recorded only at distance of 0.1-0.5 cm from the site of cutting; the electrical signal steeply decreased with the distance (Fig.…”
Section: Wounding Reactions and Passage Of Epws After Cutting The Maimentioning
confidence: 88%
“…15 EPWs are generated by mechanical and physical stimuli [16][17][18] and depend on voltage-activated and possibly mechanosensitive channels along sieve tubes. 14,19 Our recent study 13 showed, that forisomes at 3-4 cm from the stimulus site dispersed 15-45 sec after burning the leaf tip. The dispersion is reversible; the forisome recondensed after 7-15 min.…”
Section: Modes Of Sieve-plate Occlusionmentioning
confidence: 98%
See 3 more Smart Citations